Feasibility, safety and tolerability of estrogen and/or probiotics for improving vaginal health in Canadian African, Caribbean, and Black women: A pilot phase 1 clinical trial - Biban Gill; Jocelyn M. Wessels; Christina L. Hayes; Jenna Ratcliffe; Junic Wokuri; Elizabeth Ball; Gregor Reid; Rupert Kaul; Jesleen Rana; Muna Alkhaifi; Wangari Tharao; Fiona Smaill; et al. (PLoS ONE, 2025)
Background A dysbiotic vaginal microbiome (VMB) is associated with clinical conditions such as bacterial vaginosis (BV) and an increased risk of human immunodeficiency virus (HIV-1) infection. Considering the high prevalence of BV among African, Caribbean and Black (ACB) women, we conducted a prospective, randomized, open-label phase 1 clinical trial to determine the feasibility, safety and tolerability of administering low-dose estrogen, probiotics or both in combination to improve vaginal health and decrease HIV-1 susceptibility. Methods ACB women aged 18–49 from the Greater Toronto Area (GTA) were randomized to one of four study arms: intravaginal estradiol (Estring©; 7.5mg/day); a vaginal probiotic (RepHresh™ Pro-B™) administered twice daily; a combination of Estring© and vaginal RepHresh™ Pro-B™ (twice daily); or the Estring© and oral RepHresh™ Pro-B™ (twice daily), for a duration of 30 days. Feasibility was evaluated through enrolment, retention, and adherence rates, while safety and tolerability were determined by a pre- and post-treatment blood panel and reported adverse events (AEs). Results Overall, 63 ACB women were screened, 50 were enrolled and received the intervention while 41 completed the study, resulting in 80% enrollment and 82% retention rates. Overall adherence to the study protocol was high at 93%, with an adherence of 92% for RepHresh™ Pro-B™ and 97% for Estring©. A total of 88 AEs were reported by 29 participants which were mild (66/88; 75%) and largely resolved (82/88;93%) by the end of the study, with no serious AEs (SAEs) noted. In addition, a panel of safety blood markers measured pre- and post-intervention confirmed no clinically significant changes in blood chemistry or blood cell count. Conclusion Overall, the administration of intravaginal estrogen and/or probiotics in pre-menopausal ACB women is feasible, safe, and well tolerated. Trial registration The trial was registered with Clinicaltrials.gov (NCT03837015) and CIHR HIV Clinical Trials (CTN308).